Analysis of PM Magnetization Field Effects on the Unbalanced Magnetic Forces due to Rotor Eccentricity in BLDC Motors - Mahdiuon-Rad, S.; Mousavi-Aghdam, S. R.; Reza Feyzi, M.; Sharifian, M. B. B. (Engineering, Technology & Applied Science Research, 2013)
This paper investigates both static and dynamic eccentricities in single phase brushless DC (BLDC) motors and analyzes the effect of the PM magnetization field on unbalanced magnetic forces acting on the rotor. Three common types of PM magnetization field patterns including radial, parallel and sinusoidal magnetizations are considered. In both static and dynamic eccentricities, harmonic components of the unbalanced magnetic forces on the rotor are extracted and analyzed. Based on simulation results, the magnetization fields that produce the lowest and highest unbalanced magnetic forces are determined in rotor eccentricity conditions.